Peran Pos Bantuan Hukum Pada Masyarakat Kurang Mampu - Herman Balla; Suardi Suardi; Fajar Hari Sandy (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2023)
The research objectives expected by the author are First, 1. To find out the role of the Legal Aid Post in the Poor in the Sidrap Religious Court; 2. To find out the existence of legal aid posts for underprivileged communities at the Sidrap Religious Court. This research is a normative research. The collection of data used in this study was a library research (literary study) and was supported by interviews (interviews) as supporting data. Qualitatively analyzed. The results of the research show that the Legal Aid Post at the Sidrap Religious Court was formed in May 2019, and has handled 504 cases, since the issuance of the Indonesian Supreme Court Regulation Number 1 of 2014 regarding the establishment of Legal Aid Posts in every court throughout Indonesia and has handled thousands of cases. Basically in its service, the Sidrap Religious Court does not differentiate between the poor and the rich, all of whom can request legal assistance from the Legal Aid Post by completing the requirements. Based on direct interviews conducted by researchers, the poor did not know about the Legal Aid Post because they had never been involved in legal problems in court, while those who knew about the Legal Aid Post were the poor who had been involved in legal problems in court.